Alteração do ponto de injeção no desempenho de um motor agrícola operando com biocombustíveis - Paiva, Paulo Henrique (2018)
The tractor is the most used agricultural machine in the wide range of operations existing in the rural properties; being a source of mechanical energy for the operations, in which it is made available through the motor, this machine converts thermal energy into mechanics. In this context, the objective of this research was to evaluate the performance of the engine of an agricultural tractor using pure A-S500 diesel, binary (diesel-biodiesel) and ternary (diesel-biodiesel-ethanol) blends. In the case of a mechanical diesel fuel cycle engine, the injection time, known as the injection point, was also modified by changing it by 2 ° (P2), 4 ° (P4) and -2 ° (P-2), before and after the reference point of 0 ° (P0) (original of the motor), so that this moment is advanced and delayed in relation to the original. To evaluate the mechanical performance of the tractor, the data collected in this research were based on the use of a Foucault chain dynamometer coupled to the power take-off, in which the proposed diesel-biodiesel proportions were: B0, B8, B15 and B20, in (E0) and tests using the 1% (E1) ratio of this same substance. The dynamometric tests were performed with four replicates. As reference for the test and the analyzes was applied the condition B0P0E0, with 0.14% more B0P2E0 presented the best value for maximum power, B0E0P0 and B0E1P0 had the best torque values, in specific consumption B15E0P2 had a reduction of 17, 0%, already in consumption hour P-2 had better results being 10.1% of reduction. P-2 was the point of injection with better indexes of IE, RT and RR.